Plasma Membrane Permeability of Carp (Cyprinus carpio, L., 1758) Spermatozoa for Water and Cryoprotectants Molecules at Different Stages of Cryopreservation - Puhovkin, Anton Yu.; Kopeika, Evgeniy F. (Problems of Cryobiology and Cryomedicine, 2016)
Cell membrane permeability for water and cryoprotectant molecules is an important parameter to determine cooling rates during fish genetic material cryopreservation. Cell volume kinetics was assessed spectrofotometrically, the resulted experimental dependences of relative cell volume vs. time were fitted with solutions of theoretical model equations that allowed us to calculate the membrane permeability coefficients of carp spermatozoa for molecules of water and several cryoprotectants. The plasma membrane permeability coefficient of carp spermatozoa at 20°C was established to make (3.05 ± 0.40)×10–14 m3/ N·s, but when it decreased within 35...15°C temperature range the activation energy equaled to (53.9 ± 3.8) kJ/mol. A decreased membrane permeability of carp spermatozoa for dimethyl sulfoxide, ethylene glycol and 1,2-propanediol molecules within the mentioned range was characterized by the activation energy of 70–80 kJ/mol. This fact indicated that molecules of the studied substances penetrated into spermatozoon via a passive diffusion through a lipid bilayer. Our findings could be used to determine the optimal cryopreservation regimen for carp spermatozoa. Probl Cryobiol Cryomed 2016; 26(4): 340–348